2008
DOI: 10.1007/s00395-008-0728-x
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription 3 is involved in the cardioprotective signalling pathway activated by insulin therapy at reperfusion

Abstract: Objective-To evaluate the significance of the JAK-STAT pathway in insulin-induced cardioprotection from reperfusion injury. Correspondence to: Britt N. Fuglesteg, brittf@fagmed.uit.no Methods-In isolated perfused rat hearts subjected to insulin therapy (0.3 mU/ml) ± AG490 (5 μM, JAK-STAT inhibitor), the phosphorylation state of STAT3 and Akt was determined after 15 min of reperfusion. Infarct size was measured after 120 min of reperfusion. Isolated cardiac myocytes from wild type (WT) and cardiac specific STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 53 publications
2
59
0
Order By: Relevance
“…Indeed, it has been proposed that JAK/STAT activation, stimulated by postconditioning, may precede Akt phosphorylation and that JAK/ STAT phosphorylation in the absence of RISK activation is insufficient to provide protection (12). More recently, cardioprotection induced by insulin was suggested to involve a close interaction between STAT3 and Akt (11). This area of investigation is, however, still in its early stages, and whether JAK-STAT signaling operates upstream of the RISK pathway, in relation to cardioprotection, or the two pathways operate in parallel remains to be established definitively.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been proposed that JAK/STAT activation, stimulated by postconditioning, may precede Akt phosphorylation and that JAK/ STAT phosphorylation in the absence of RISK activation is insufficient to provide protection (12). More recently, cardioprotection induced by insulin was suggested to involve a close interaction between STAT3 and Akt (11). This area of investigation is, however, still in its early stages, and whether JAK-STAT signaling operates upstream of the RISK pathway, in relation to cardioprotection, or the two pathways operate in parallel remains to be established definitively.…”
Section: Discussionmentioning
confidence: 99%
“…22 Sphingosine kinase-1, the key enzyme that catalyzes the formation of sphingosine-1-phosphate, is also important for postconditioning in mice, 23 and sphingosine kinase activation is probably mediated by STAT3. 24 Whereas the present study revealed major differences in signal transduction by RISK between rodents and pigs, both sphingosine 25 and STAT3 26 are parts of the signal transduction of tumor necrosis factor (TNF)␣-induced cardioprotection, TNF␣-induced cardioprotection does not rely on AKT and ERK1/2, 26 and TNF␣ is also cardioprotective in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathways are responsive to a large number of cytokines, growth factors and hormones and play a vital role in mediating cardioprotection from IR injuries [5,17,22]. Experimental evidence indicates that the JAK2/STAT3 signaling pathway is specifically involved in preventing myocardial IR injury [21,25].…”
Section: Introductionmentioning
confidence: 99%